Dual Caregivers of Persons living with Dementia: The Added Stress of COVID-19 Pandemic. (17th February 2022) - Atkinson, Emily; Savla, Jyoti; Roberto, Karen A.; Blieszner, Rosemary; McCann, Brandy R.; Knight, Aubrey L.
Serving in dual caregiving roles presents challenges and has consequences for caregivers' physical and mental health. Forty-six dual caregivers in rural southwest Virginia participated in one semi-structured telephone interview pre-pandemic. Of these caregivers, nine dual caregivers of multiple older adults (MOA) and six caregivers of multiple generations (MG) participated in two telephone interviews during the COVID-19 pandemic. Pre-pandemic health, stress, and support data were used to compare dual caregivers of MOA and MG; differences were minimal. Responses to interviews conducted during the pandemic highlighted the effects of social restrictions on MOA and MG caregivers, revealing five themes (1) Increased isolation, (2) Increased need for vigilance, (3) Negative impact on mental health, (4) Tendency to "do it all, " and (5) Increased informal help. MOA and MG caregivers differed on managing care responsibilities and ensuring the health of care recipients. In general, dual caregivers experienced decreased mental health, increased social isolation, and increased caregiving responsibilities. Antecedents of the pandemic experiences differentiated MOA and MG caregiver. Findings suggest that programs and services should target dual caregivers' unique needs.